ANALISIS PENGELOLAAN DANA DESA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KECAMATAN LANGSA KOTA KOTA LANGSA - FAHRUL RIDHA (Universitas Islam Negeri Sumatera Utara, 2019)
This research is to find out how to manage village funds and how to improve village governance in improving the economy of the people in Langsa Kota District. This study uses a qualitative descriptive research method. The results of the study found that Village Fund Management has been running effectively, while its allocation has not been 100% effective. The government's efforts to improve the community economy are by empowering, among others, in the field of infrastructure, empowerment in the general and religious fields. empowerment in the field of infrastructure is by making trenches, roads, making fishing nets or nets and making cakes and embroidery. for community empowerment in general and religious fields. In the general field, the existence of the PKK is realized. In the religious field, it was realized by holding regular recitations and training for tahyiz mayit.